Consumer perceptions of luxury brands: An owner-based perspective. Issue 3 (June 2019) - Bachmann, Frank; Walsh, Gianfranco; Hammes, Eva K.
Abstract: To deepen theoretical and practical understanding of consumers' perceptions of luxury brands, prior marketing literature has investigated the financial, functional, individual, and social dimensions of the luxury value construct. However, it has not considered the owners of luxury brands or detailed the moderated effects of luxury value on related attitudinal outcomes. To address this gap, this study draws on an existing second-order conceptualization of luxury value to introduce and empirically examine an extended conceptualization of the owner-based luxury value (OBLV) construct. The study draws on brand equity theory to offer a conceptual model of the attitudinal outcomes of OBLV in terms of brand loyalty, brand attachment, brand community behavior, and brand engagement. Using unique data from 452 actual owners of three luxury brands (Cartier, Louis Vuitton, and Prada), the authors confirm the predicted attitudinal outcomes of OBLV and reveal moderating effects of awareness of counterfeit existence. Their findings provide new insights and implications for luxury brand research and luxury brand managers. The research provides a richer understanding of OBLV and yields important managerial insights into how to influence luxury-seeking consumers' perceptions of, and attitudes to, luxury brands.